New records of introduced species in the Mediterranean Sea (December 2025) - MICHEL BARICHE; SHAHENAZ M. ABD ELLAH; OKAN AKYOL; EMAN SALEM ALFERGANI; ANDREA ALVITO; FIRAS ALSHAWY; IZDIHAR ALI AMMAR; ÉRICA CAROLINE BECKER; GIAMBATTISTA BELLO; DAMLA BETON; SENEM ÇAĞLAR; GIOVANNI CANDUCI; et al. (Mediterranean Marine Science, 2025)
New records of introduced species in the Mediterranean Sea (December 2025)

The Distribution of Pseudodiaptomus marinus in European and Neighbouring Waters—A Rolling Review - Marco Uttieri; Olga Anadoli; Elisa Banchi; Marco Battuello; Şengül Beşiktepe; Ylenia Carotenuto; Sónia Cotrim Marques; Alessandra de Olazabal; Iole Di Capua; Kirsten Engell-Sørensen; Alenka Goruppi; Tamar Guy-Haim; et al. (Journal of Marine Science and Engineering, 2023)
Among non-native copepods, the calanoid Pseudodiaptomus marinus Sato, 1913 is the species probably spreading at the fastest pace in European and neighbouring waters since its first record in the Adriatic Sea in 2007. In this contribution, we provide an update on the distribution of P. marinus in the Mediterranean and Black Seas, along the Atlantic coasts of Europe, in the English Channel and in the southern North Sea. Starting from a previous distribution overview, we include here original and recently (2019–2023) published data to show the novel introduction of this species in different geographical areas, and its secondary spreading in already colonised regions. The picture drawn in this work confirms the strong ability of P. marinus to settle in environments characterised by extremely diverse abiotic conditions, and to take advantage of different vectors of introduction. The data presented allow speculations on realistic future introductions of P. marinus and on the potential extension of its distribution range.

New Mediterranean Biodiversity Records 2019 - BRANCO DRAGIČEVIĆ; OLGA ANADOLI; DROR ANGEL; MOULOUD BENABDI; GHAZI BITAR; LUCA CASTRIOTA; FABIO CROCETTA; ALAN DEIDUN; JAKOV DULČIĆ; DOR EDELIST; VASILIS GEROVASILEIOU; SALVATORE GIACOBBE; et al. (Mediterranean Marine Science, 2019)
This paper is a collection of novel distributional records of 20 species belonging to 8 phyla (Chlorophyta, Rhodophyta, Cnidaria, Ctenophora, Annelida, Mollusca, Arthropoda and Chordata) from 11 Mediterranean countries, namely, Spain: an additional record of the Canary dentex Dentex canariensis is reported from Spain (Valencia), this is the northernmost record of this species in the Mediterranean; Algeria: the first documented record of Caulerpa chemnitzia is reported from the Algerian coast; France: the first record of the Spotted sea hare Aplysia dactylomela is reported from the eastern coast of Corsica; Italy: the first records of the Lessepsian polychaete Dorvillea similis and the alien bivalve Isognomon legumen are reported from Italian waters while additional records of Mnemiopsis leidyi in the south Adriatic are provided; Libya: the first record of an alien mollusc Crepidula fornicata is reported from Libyan waters; Malta: multiple sightings of gelatinous species Apolemia uvaria, Phacellophora camtschatica and Physophora hydrostatica are reported for the first time from Maltese waters, as well as the first tentative record of the Orange-spotted grouper Epinephelus cfr. coioides; Greece: an occurrence of a rare Bigeye thresher shark Alopias superciliosus is reported from Hellenic Ionian waters, while the first records of the alien Mertens’ prawn-goby Vanderhorstia mertensi, the recently described cyclopoid copepod Oithona davisae and the alien red seaweed Asparagopsis armata are reported from the Aegean Sea. The presence of the micromollusc Euthymella colzumensis is confirmed for Greece; Cyprus: the first record of the red cornetfish Fistularia petimba is reported from Cyprus; Turkey: the first record of the alien jellyfish Marivagia stellata is reported from south-eastern Turkey; Israel: the first records of the sea nettle Chrysaora sp. in the Levant are reported.